Pengetahuan, Sikap dan Penerimaan Vaksin COVID-19 di Kabupaten Sidenreng Rappang - Ayu Fitriani; Nurani St Juwaeriyah AM; Nurul Arfah Ilman; Nurdini Nurdini; Nurul Ainy Mansul S; Fadli Fadli (FORIKES, 2022)
The COVID-19 vaccine can reduce the spread of the disease in a population because the vaccine protects not only those who have been vaccinated but also the wider community. The purpose of this study was to determine the knowledge and attitudes of the community towards the process of receiving the COVID-19 vaccine. This study was a quantitative research with a cross-sectional design, involving 103 respondents. Data were collected through filling out a questionnaire and then analyzed using the Chi-square test. The results of this study indicated a p value = 0.022 for the relationship between knowledge and the process of receiving the COVID-19 vaccine and 0.000 for the relationship between attitudes and the process of receiving vaccines. Furthermore, it was concluded that knowledge and attitudes were significantly related to the acceptance of the COVID-19 vaccine.Keywords: COVID-19; receipt of vaccines; knowledge; attitude ABSTRAK Vaksin COVID-19 dapat mengurangi penyebaran penyakit dalam suatu populasi karena vaksin tidak hanya melindungi mereka yang sudah divaksinasi tetapi juga masyarakat luas. Tujuan penelitian ini adalah untuk mengetahui pengetahuan dan sikap masyarakat terhadap proses penerimaan vaksin COVID-19. Penelitian ini merupakan penelitian kuantitatif dengan desain cross-sectional, yang melibatkan 103 responden. Data dikumpulkan melalui pengisian kuesioner lalu dianalisis menggunakan uji Chi-square. Hasil penelitian ini menunjukkan nilai p = 0,022 untuk hubungan antara pengetahuan dengan proses penerimaan vaksin COVID-19 dan 0,000 untuk hubungan antara sikap dengan proses penerimaan vaksin. Selanjutnya disimpulkan bahwa pengetahuan dan sikap berhubungan secara signifikan dengan penerimaan vaksin COVID-19.Kata kunci: COVID-19; penerimaan vaksin; pengetahuan; sikap